Institutional Factors and Student Satisfaction of Post-graduate Adult Learners - Koivisto, Matti (International Journal of Advanced Corporate Learning (iJAC), 2024)
In recent years, various stakeholders, including researchers, policymakers, and students, have displayed a growing interest in assessing the effectiveness and performance of higher education institutions. Although no single indicator is sufficient to describe the organizational quality of the university, student satisfaction is one of the most often used indicators. Extensive prior research has consistently demonstrated that high levels of student satisfaction positively influence crucial performance measures such as student retention and institutional graduation rates. Although student satisfaction has been extensively studied, particularly among undergraduate students, much less research has been done among adult learners returning to college. This paper aims to identify the key institutional factors that significantly impact the satisfaction of part-time postgraduate students. We hope that the insights of the study can help universities to allocate their limited resources and ultimately to enhance the well-being of the students.